Diagnosis and treatment of aseptic femoral head necrosis - Jonibekov Jasur Jonibekovich (Genius Journals, 2021)
Aseptic femoral head necrosis is a multifactorial disease characterized by the occurrence of femoral head collapse with progressive development of severe secondary coxarthrosis. Clinically, the disease is manifested by progressive pain and limited range of motion, Trendelenburg's symptom, crepitation and instability of the femoral head. Treatment includes surgical interventions and correction of cytoactivity. There is evidence of the ability of bisphosphonates to prevent femoral head collapse.
Keywords: Aseptic femoral head necrosis; osteonecrosis; Leiden factor V; interleukin